Transformational Leadership, Organizational Culture, and Member Performance: The Mediating Role of Motivation - Arif Akbarurrijal; Nur Hidayati; Nurhidayah Nurhidayah (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the influence of transformational leadership and organizational culture on member performance, with motivation as a mediating variable. Using a quantitative approach, data were collected through questionnaires from 187 members of the Islamic Students Association (HMI) Malang Branch. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational culture has a positive and significant influence on member performance and motivation. Transformational leadership has a positive and significant influence on member performance but does not have a significant influence on motivation. Motivation has a positive and significant influence on member performance. Furthermore, motivation mediates the relationship between organizational culture and member performance, but does not mediate the relationship between transformational leadership and member performance. These findings suggest that organizational culture and transformational leadership are important for improving member performance, but the role of motivation as a mediator is only confirmed for organizational culture in the context of voluntary and non-profit student organizations. This study contributes to the literature by clarifying the mediating role of motivation in the context of student organizations.